Obesity and Lower Extremity Reconstruction: Evaluating Body Mass Index as an Independent Risk Factor for Early Complications - Rifkin, William J.; Kantar, Rami S.; Daar, David A.; Alfonso, Allyson R.; Cammarata, Michael J.; Wilson, Stelios C.; Diaz-Siso, J. Rodrigo; Levine, Jamie P.; Stranix, John T.; Ceradini, Daniel J. (Journal of Reconstructive Microsurgery, 2019)
Background The prevalence of obesity in the United States continues to grow and is estimated to affect over a quarter of the working-age population. Some studies have identified obesity as a risk factor for flap failure and complications in free flap-based breast reconstruction, but its clinical significance is less clear in nonbreast reconstruction. The role of obesity as a risk factor for failure and complications following lower extremity reconstruction has not been well described, and the limited existing literature demonstrates conflicting results.Methods The American College of Surgeons National Surgical Quality Improvement Program database was reviewed to identify patients undergoing local- or free-flap reconstruction of the lower extremity between 2010 and 2015. Preoperative variables and outcomes were compared between obese (body mass index ≥ 30) and nonobese patients. Chi-square analysis and Fisher's exact test were used for categorical variables and t-tests for continuous variables. Multivariate regression was performed to control for confounders.Results Univariate analysis of medical and surgical outcomes revealed that obese patients undergoing local flaps of the lower extremity required a significantly longer operative time (187.7 ± 123.2 vs. 166.2 ± 111.7 minutes; p = 0.003) and had significantly higher rates of superficial surgical site infection (SSI; 7.2% vs. 4.5%; p = 0.04). On univariate analysis, there were no significant differences in any postoperative outcomes between obese and nonobese patients undergoing microvascular free flaps of the lower extremity.On multivariate regression analysis, obesity was not an independent risk factor for superficial SSI (odds ratio = 1.01, p = 0.98) or increased operative time (β  = 16.01, p = 0.14) for local flaps of the lower extremity.Conclusion Evaluation of a large, multicenter, validated and risk-adjusted nationwide cohort demonstrated that obesity is not an independent risk factor for early complications following lower extremity reconstruction, suggesting that these procedures may be performed safely in the obese patient population.
Keywords: obesity; body mass index; lower extremity reconstruction